2022
DOI: 10.1002/rev3.3336
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the range and evidence‐base of interventions in a cluster of schools

Abstract: The last decade has seen an increased focus through policy and research for schools to move towards an evidence‐informed practice. Although some practitioners now access the external research evidence when deciding which interventions to adopt in their school, research suggests many still do not. Instead, approaches to teaching and learning are often informed by trends and the opinions and experiences of practitioners. Little is known about what intervention programmes/approaches are used in schools and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 162 publications
(215 reference statements)
2
6
0
Order By: Relevance
“…We should be wary of the widespread adoption of programmes that lack robust evaluations and/or cannot be shown to work in everyday school settings (Pegram et al, 2022). Over the years, research has found several widely adopted educational theories such as learning styles (Evidence for Learning, n.d.; Pashler et al, 2009) and brain training apps (Spaulding et al, 2010; Stephenson, 2009) to have little positive impact on learner outcomes and/or be theoretically flawed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We should be wary of the widespread adoption of programmes that lack robust evaluations and/or cannot be shown to work in everyday school settings (Pegram et al, 2022). Over the years, research has found several widely adopted educational theories such as learning styles (Evidence for Learning, n.d.; Pashler et al, 2009) and brain training apps (Spaulding et al, 2010; Stephenson, 2009) to have little positive impact on learner outcomes and/or be theoretically flawed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Pegram et al (2022) identified 138 different interventions in use across a cluster of 10 schools—67% of these interventions had no published research evidence to support them and only 11% had promising evidence of positive causal impact on pupil outcomes. This poses important questions around why some schools adopt and use interventions with a limited evidence‐base, and whether it is even practical to implement multiple interventions to a high level of fidelity.…”
Section: The Evidence‐building Framework For Education: Conceptualisi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat depressingly, Pegram et al (2022) show us that most programmes and interventions used in schools are not evidence-led, and some are harmful. Of 242 interventions used in a cluster of schools, only 30% had any evidence of benefit.…”
Section: Do Users Actually Use E Vidence?mentioning
confidence: 99%
“…Evidence-based practice (EBP) has become a standard of care in psychology (see APA Presidential Task Force on Evidence-Based Practice, 2006); however, EBP has not yet become a standard of practice in the field of education. There have been increasing calls to close the gap between research and practice in education, as studies have identified a disparity between educational research and practice both at the policy level and in schools (see Anwer & Reiss, 2022; Broekkamp & van Hout-Wolters, 2007; Pegram et al, 2022). This discrepancy was most recently exemplified by the Ontario Human Rights Commission’s (2022) Right to Read Report, which described the poor literacy outcomes resulting from a lack of evidence-based reading instruction in the provincial curriculum.…”
mentioning
confidence: 99%